Avaliação dos programas de quimioprofilaxia voltados para doenças negligenciadas e da pobreza na América Latina - Cordeiro, Wilcare de Medeiros (2024)
Infectious diseases have a profound and historical impact on societies, affecting communities' health and social and economic structure. The World Health Organization emphasizes that infectious diseases not only cause loss of life but also high levels of morbidity. Control strategies for these diseases are essential to reduce inequalities, poverty, and the emergence of disabilities. Identifying different types of chemoprophylactic interventions is fundamental for these diseases to be controlled or eliminated. The thesis was developed by writing two studies that were published in article format. The first study was a systematic review to evaluate existing chemoprophylaxis programs in Latin America. Of the fifteen neglected diseases in the Americas listed by the Pan American Health Organization, there are chemoprophylaxis programs for fascioliasis, lymphatic filariasis, leprosy, onchocerciasis, schistosomiasis, soil- transmitted helminths, and trachoma. The findings highlight the vital role of chemoprophylaxis in public health in combating diseases such as filariasis, onchocerciasis, schistosomiasis, tuberculosis, leprosy, and soil-transmitted helminths. Therefore, continuous research and improvement of chemoprophylactic regimens are essential to address and overcome current obstacles, further supporting global initiatives to manage and eradicate these diseases. The second study used Monte Carlo, pharmacokinetic simulation models. It aimed to evaluate the expected effect of rifampicin induction on the apparent oral clearance of oral contraceptives, which have the potential to be used in chemoprophylaxis. It was observed that drug interactions between oral contraceptives and rifampicin are not clinically relevant when administered as part of post-exposure prophylaxis for leprosy. Additionally, the use of other contraceptive methods is not necessary for the prevention of future pregnancies. The results of study 2 are encouraging for women who want to prevent leprosy and wish to continue using oral contraceptives as a form of contraception.